In a Heartbeat: Light and Cardiovascular Physiology - Chellappa, Sarah L.; Lasauskaite, Ruta; Cajochen, Christian (Frontiers in Neurology, 2017)
Light impinging on the retina fulfils a dual function: it serves for vision and it is required for proper entrainment of the endogenous circadian timing system to the 24-h day, thus influencing behaviors that promote health and optimal quality of life but that are independent of image formation. The circadian pacemaker located in the suprachiasmatic nuclei modulates the cardiovascular system with an intrinsic ability to anticipate morning solar time and with a circadian nature of adverse cardiovascular events. Here we infer that light exposure might affect cardiovascular function and provide evidence from existing research. Findings show time-of-day dependent increase in relative sympathetic tone associated with bright light in the morning but not in the evening hours. Furthermore, dynamic light in the early morning hours can reduce the deleterious sleep-to-wake evoked transition on cardiac modulation. On the contrary, effects of numerous light parameters, such as illuminance level and wavelength of monochromatic light, on cardiac function are mixed. Therefore, in future research studies, light modalities, such as timing, duration and its wavelength composition, should be taken in to account when testing the potential of light as a non-invasive countermeasure for adverse cardiovascular events.